Reinforcements how to get people to help you - Halvorson, Heidi Grant- 1973- (Harvard Business Review Press, 2018)
We all need help--especially in today's uber-collaborative workplaces. Here's the good news: humans are naturally wired to want to help each other. Now here's the bad: asking for help makes most of us wildly uncomfortable. As a result, we do a poor job of calling in the reinforcements we need, leaving confused or even offended colleagues in our wake. This pragmatic book explains the research on what psychologists call social intelligence. To elicit helpful behavior from their colleagues, you need to do two things: 1) Remove the obstacles that stand in the way of them helping you; 2) Trigger one or more of the motivations that make people want to help. Whether you're a first-time manager or a seasoned leader, getting people to do things for you is what management is. This book will help you do so, and do it in a way that leaves your helpers feeling good about pitching in.--Provided by publisher.